New Media, Digitalization, and the Evolution of the Professional Sport Industry - Zheng, Jingxuan; Mason, Daniel S. (Frontiers in Sports and Active Living, 2022)
The professional sport industry achieved tremendous success in the traditional broadcast media age, established a multi-sided market and an effective business model for revenue growth. However, the emergence and proliferation of the new media technologies have drastically changed the media landscape, creating a much more complicated cross-media environment that unites popularity and personalization, structure and agency. Such a changing environment creates transformations within the professional sport industry, and adapting to these transformations will lead to the evolution of the professional sport industry and its success in the digital media age.